The effect different of hydrochloric acid concentrations on the cleaning of Ni foam substrate: structural and morphological studies - Abu Bakar, Nor Atikah; Salleh, Nor Azmira; A. Hamid, Noor Ashrina; Che Abdullah, Che Azurahanim; Wan Rahiman; Basirun, Wan Jeffrey; Kheawhom, Soorathep; Mohamad, Ahmad Azmin (Elsevier, 2022)
Recently, much attention has been focused on nickel (Ni) as current collectors for supercapacitor applications. The cleaning of Ni current collector is mandatory before it can be utilized in supercapacitor devices. The cleaning of the Ni foam substrate is essential for removing contaminations and modifying the surface morphology of the foam. In this study, Ni foam substrates were cleaned via sonication in different concentrations of HCl solution and the formation of the oxide layer on the surface of the Ni foam was investigated. The formation of oxide layer on the Ni foams was characterized of its morphology, elemental and structural analyses. The cleaning of the Ni foam with HCl solution leads to the formation of oxide layer on the Ni foam surface. The cleaning of Ni foam substrate with a 2.5 M of HCl solution gave an oxide layer with uniform thickness (0.034 μm) before the layer was detached. Cleaning with 5.0 M HCl concentration produced the thickest oxide layer formation (0.327 μm). However, a cracked line (black line) was also observed for 4.0 and 5.0 M HCl concentrations, indicating that the attachment of these oxide layers on the surface of the Ni foam was poor and susceptible to detachment. From the structural analyses, no impurity peaks were detected in the diffraction pattern and the intensity peaks of Ni were decreased and broaden with the increase in the HCl concentration. It is proven that the Ni foam have uniform surface roughness of the oxide layer when cleaned with HCl solution lower than 2.5 M but the thick oxide layer was detached at concentrations higher than 2.5 M which deteriorates the supercapacitor systems.